(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Three years experiment was conducted to establishment the BAUGPC released BAU Sapota-1 at three selected upazilla of Northern region and BAUGPC, Mymensingh of Bangladesh during the period from July 2009 to June 2013. Among the locations, Palashbari, Gaibandha exhibited the tallest plant, maximum leaves, maximum branches and higher canopy in all the years (2010, 2011 and 2012), Palashbari, Gaibandha also noticed the minimum time for fruit setting, maximum harvested fruit and fresh fruits as well as the higher fruit yield of BAU Sapota1 compared to other locations. The overall results suggest that BAU Sapota-1 can be recommended to cultivate in the Palashbari Gaibandha area for obtaining higher yields. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21243 J. Bangladesh Agril. Univ. 12(1): 61-65, June 2014